PEMBAGIAN KERJA, MOTIVASI KERJA DAN KEMAMPUAN KERJASAMA TERHADAP EFEKTIVITAS KERJA PEGAWAI - Hikmawati, Allien; Sawiji, Hery; Subarno, Anton (Pendidikan Administrasi Perkantoran FKIP Univesitas Sebelas Maret, 2012)
Abstract: The objectives of this research are to investigate: (1) the direct effect of the work division on the employees? work effectiveness; (2) the direct effect of the work motivation on the employees? work effectiveness; (3) the direct effect of the cooperation ability on the employees? work effectiveness; (4) the indirect effect of the work division on the employees? work effectiveness through the cooperation ability; and (5) the indirect effect of the work motivation on the employees? work effectiveness through the cooperation ability at the Limited Liability Company of PT. Pos Indonesia (Persero) Surakarta in 2012. his research used the quantitative research method. The population of the research was all of the employees of the Limited Liability Company of PT. Pos Indonesia (Persero) Surakarta in 2012. The samples of the research were 53 employees or 25% of the total number of employees of the company, and they were taken by using the proportional random sampling technique. The data of the research were gathered through questionnaire supported by documentation method. The data of the research were analyzed by using the path analysis with the computer program of SPSS 17. The results of the research are as follows: (1) there is a significant and positive direct effect of the work division on the employees? work effectiveness as indicated by the value of ? YX1 = beta = 0.356 with the probability (sig) = 0.003; (2) there is a positive and significant direct effect of the work motivation on the employees? work effectiveness as shown by the value of ? YX2 = beta = 0.342 with the probability (sig) = 0.003; (3) there is a positive and significant direct effect of the cooperation ability on the employees? work effectiveness as pointed out by the value of ? YX3 = beta = 0.240 with the probability (sig) = 0.046; (4) there is a positive and significant indirect effect of the work division on the employees? work effectiveness through the cooperation ability as suggested by the value of ? X3X1 . ? YX3 = (0.308) . (0.240) = 0. 074; and (5) there is a positive and significant indirect effect of the work motivation on the employees? work effectiveness through the cooperation ability as specified by the value of ? X3X2 . ? YX3 = (0.277) . (0.240) = 0. 066.Keywords: Work division, work motivation, cooperation ability, and work effectiness.